PERBEDAAN PEMBERIAN AIR JAHE DAN AIR KELAPA TERHADAP PENURUNAN NYERI HAID PADA REMAJA PUTRI DI SMAN 3 MAKASSAR TAHUN 2020 - Syamsuryanita Syamsuryanita; Nurul Ikawati (Sekolah Tinggi Pariwisata Mataram, 2022)
Menstrual pain is a medical condition that occurs during menstruation or menstruation that can interfere with activities and requires medication characterized by pain or pain in the abdominal or pelvic area. ginger and coconut water therapy is one of the non- pharmacological actions to relieve or reduce menstrual pain. this study aims to determine the differences in giving ginger and coconut water to reduce menstrual pain in young girls at sma negeri 3 makassar in 2020. the method used in this study is the quasi experiment method with a post test only control group design approach. the population in this study were 101 female students and the sample taken in this study was 30 students with a purposive sampling technique. the research process used an observation sheet using a pain level measurement, namely the numeral rating scale (nrs). the results of this study obtained an average value of 0.47 ginger water and an average value of coconut water 1.00 with the mann-withney test with a value of ρ = 0.013> α = 0.05, which means that there is a difference in the provision of ginger water and coconut water to reduce menstrual pain in young women at sman 3 makassar in 2020, where ginger water is more effective in reducing menstrual pain than coconut water.